Analysis of expression of selected genes coding transcriptional activators in ductal breast cancer cells in vitro treated with paclitaxel - Ziaja-Sołtys, Marta; Rzymowska, Jolanta (Contemporary Oncology/Współczesna Onkologia, 2011)
Aim of the study : The aim of our studies was to assess the influence of paclitaxel on the expression of selected activating transcriptional factors in ductal breast cancer primary cells using the microarray technique. Material and methods : The cells were treated with 60 ng/ml and 300 ng/ml doses of paclitaxel. Administered dose concentrations corresponded to those applied in breast cancer mono- and polytherapy and also covered the number of chemotherapy cycles. The control breast cancer cells in vitro were not treated with a cytostatic drug. Results : Sixteen among 21 analysed genes indicated statistically significant increased expression in the cells incubated with 60 ng/ml of paclitaxel: 15 genes in the 1.8-3.3 fold range (p < 0.05), but ETS1 gene expression level increased 4.7-fold in comparison to the control cells. The higher dose of 300 ng/ml of paclitaxel caused a cytotoxic effect in the cells and a statistically non-significant decrease in expression of all studied genes. Conclusions : In summary it may be stated that a 60 ng/ml dose of paclitaxel caused increased expression of analysed genes coding transcriptional activating factors that enhance the studied taxane’s mechanism of action. Thus we can suppose that these changes in gene expression values may constitute prognostic and predictive factors in ductal breast cancer therapy. The obtained results encourage us to carry out further studies on the functions and relations between genes and their products.